Making our own destiny : single women, opportunity, and family in Shanghai, Hong Kong, and Tokyo - Nakano, Lynne Y., 1965- (University of Hawai'i Press, 2022)
In East Asia's largest cities, hundreds of thousands of women remain single into middle age and beyond, giving rise to a demographic transformation with profound implications for their societies. Labeled in the media as "loser dogs" and "parasites" in Japan and "leftover women" in mainland China and Hong Kong, single women in East Asia are criticized for being choosy, selfish, and overly independent. Based on ethnographic research and interviews with more than a hundred single women in Shanghai, Hong Kong, and Tokyo, Making Our Own Destiny is the first study to comprehensively compare the views and experiences of single women living in these three great cities--cities that stand at the forefront of the region's movement toward later marriage and rising singlehood.This well-researched book explores how single women attempt to take advantage of unprecedented opportunities for success in education and work while navigating marriage and family expectations. Unlike their counterparts in Europe and North America, many do not have romantic partners and most do not have children. What do these women want? How do they see themselves and their place in society? What are their values, goals, and dreams? As they work to balance opportunities with expectations, single women in urban East Asia find themselves deeply embedded in the caregiving systems of their societies. In Shanghai, author Lynne Nakano finds single women rushing to marry to enter intergenerational relationships of care. In Hong Kong, they consider the risks of marriage as they tend to the needs of natal and extended families. In Tokyo, many single women hope to marry to have children while others find a place for themselves in their families as elder caregivers.Nakano's intimate portrayals not only expose meticulously planned family strategies gone awry, engagements broken, and careers abandoned, but also highlight the experiences of women embracing the joys of remaining single. Hers is a fascinating study of modern women finding meaning in their lives while offering an insightful glimpse into the future of urban families in an age of low fertility and long transitions into adulthood.